Rapid vegetative propagation of Stylosanthes guianensis - Miles, John W. (1982)
The effects of size of terminal stem cuttings (2-, 3-, or 4-leaf) and of auxin treatment on percent rooting, root number and root length of six Stylosanthes guianensis accessions were evaluated in a single, factorial experiment. Overall, 66% of cuttings rooted within ten days. Accessions differed greatly in rooting ability. Auxin treatment increased rooting markedly. The smallest cuttings rooted as well as, or better than, larger cuttings. The results suggest a simple method for rapid vegetative propagation of S. guianensis seedlings for initial increase of new introductions for which the seed is scarce or for exact replication of genotypes for genetic or breeding studies